Thrombosis-associated hypofibrinogenemia: novel abnormal fibrinogen variant FGG c.8G>A with oxidative posttranslational modifications - Ceznerová, Eliška; Kaufmanová, Jiřina; Stikarová, Jana; Pastva, Ondřej; Loužil, Jan; Chrastinová, Leona; Suttnar, Jiři; Kotlín, Roman; Dyr, Jan Evangelista (Blood coagulation & fibrinolysis, 2022)
Here, we present the first case of fibrinogen variant FGG c.8G>A. We investigated the behaviour of this mutated fibrinogen in blood coagulation using fibrin polymerization, fibrinolysis, fibrinopeptides release measurement, mass spectrometry (MS), and scanning electron microscopy (SEM). The case was identified by routine coagulation testing of a 34-year-old man diagnosed with thrombosis. Initial genetic analysis revealed a heterozygous mutation in exon 1 of the FGG gene encoding gamma chain signal peptide. Fibrin polymerization by thrombin and reptilase showed the normal formation of the fibrin clot. However, maximal absorbance within polymerization was lower and fibrinolysis had a longer degradation phase than healthy control. SEM revealed a significant difference in clot structure of the patient, and interestingly, MS detected several posttranslational oxidations of fibrinogen. The data suggest that the mutation FGG c.8G>A with the combination of the effect of posttranslational modifications causes a novel case of hypofibrinogenemia associated with thrombosis.
Keywords: fibrinogeny abnormální; trombóza; Afibrinogenemia; Male; Fibrinogens, Abnormal; Fibrin; Protein Processing, Post-Translational; Oxidative Stress; Thrombosis; mužské pohlaví; Adult; posttranslační úpravy proteinů; fibrin; oxidační stres; Fibrinogen; hemostatika; fibrinogen; afibrinogenemie; dospělí; lidé; Humans; Hemostatics